Role of goblet cell protein CLCA1 in murine DSS colitis. Issue 1 (December 2016) - Erickson, Nancy; Mundhenk, Lars; Giovannini, Samoa; Glauben, Rainer; Heimesaat, Markus; Gruber, Achim
Abstract Background The secreted goblet cell protein CLCA1 (chloride channel regulator, calcium-activated-1) is, in addition to its established role in epithelial chloride conductance regulation, thought to act as a multifunctional signaling protein, including cellular differentiation pathways and induction of mucus production. Specifically, CLCA1 has recently been shown to modulate early immune responses by regulation of cytokines. Here, we analyze the role of CLCA1, which is highly expressed and secreted by colon goblet cells, in the course of murine dextran sodium sulfate-induced colitis. Findings We comparedClca1 -deficient and wild type mice under unchallenged and DSS-challenged conditions at various time points, including weight loss, colon weight-length-ratio and histological characterization of inflammation and regeneration. Expression levels of relevant cytokines, trefoil factor 3 and E-cadherin were assessed via quantitative PCR and cytometric bead arrays. Lack of CLCA1 was associated with a more than two-fold increased expression ofCxcl-1 - andIl-17 -mRNA during DSS colitis. However, no differences were found betweenClca1 -deficient and wild type mice under unchallenged or DSS-challenged conditions in terms of clinical findings, disease progression, colitis outcome, epithelial defects or regeneration. Conclusions CLCA1 is involved in the modulation of cytokine responses in the colon, albeit differently than what had been observed in the lungs. Obviously, the pathways involved depend on the type of challenge, time point or tissue environment.